Feasibility of narrative exposure therapy in an outpatient day treatment programme for refugees: improvement in symptoms and global functioning. Issue 1 (31st December 2020) - de la Rie, Simone M.; Smid, Geert E.; van der Aa, Niels; van Est, Leanne A. C.; Bisseling, Eef; Boelen, Paul A.
ABSTRACT: Background:  Refugees are at high risk for developing post-traumatic stress disorder (PTSD). Narrative exposure therapy (NET) is an evidence-based treatment of PTSD, designed for patients exposed to (multiple) traumatic events and recommended for patients with culturally diverse backgrounds. In clinical practice,  adherence to the NET-protocol has been challenged because of psychosocial complexities and comorbid disorders.  Objective: : The current study investigated the feasibility of NET embedded in an outpatient day treatment programme for refugees and examined reduction in PTSD symptoms and improvement of global functioning as well as correlates of change.  Method: Participants were patients who consecutively entered an outpatient daytreatment programme from 2013-2017. The majority had a history of prior unsuccessful treatment. PTSD was assessed with the Clinically Administered PTSD Scale (CAPS) before and after finishing NET. Global Assessment of Functioning (GAF) was used to examine changes in functioning. Changes in PTSD scores and functioning were analyzed using paired t-tests and reliable change indices. Patients showing significant improvement were compared to those who did not,  on patient and treatment characteristics, including sex, age, region of origin, childhood trauma and treatment duration and dosage of NET.  Results: : Of 97 patients, 76 (78.4%) completed NET. Completers had a longer residency and were more likely to have a partner. Significant reductions in PTSD symptoms and improvements in global functioning were observed. Twenty-eight percent showed reliable improvement with large effect sizes. Four patients did no longer meet the criteria for PTSD. No strong moderators for changes were found. Patients who did not improve more often had a history of childhood trauma. Conclusions: NET embedded in an outpatient day treatment programme appears to be feasible. In those who improved, a substantial decline in symptoms and improvement of functioning were observed. The findings suggest that a socially supportive living environment enhances acceptability of trauma-focused treatment in refugees.